From Scroll to Speak: A Quasi-Experimental Study of How TikTok and Instagram Reels Influence Students’ Confidence in Speaking English - Awaliyah Rohmah; Irmayani Irmayani (LPPM Universitas Islam Darul `Ulum Lamongan, 2025)
This study looks at how short-form video platforms—more especially, TikTok and Instagram Reels—have affected students' English language confidence. This study was driven by the growing prevalence of social media among adolescents and its possible role as a medium for expressive, communicative, and reflective learning. A quasi-experimental design of the non-equivalent control group type was used in a quantitative approach. 30 eighth-graders from a junior high school in Turi, Lamongan, participated in the study. They were split into 2 groups: 15 in the experimental group and 15 in the control group. Speaking exercises and a Likert-scale confidence questionnaire were included in the pre-test and post-test used to collect data. Using SPSS version 26, the data was analysed using paired sample t-tests, independent sample t-tests, descriptive statistics, and normality and homogeneity tests, The findings indicated a notable enhancement in the experimental group, which achieved a post-test average of 77.13, in contrast to 65.20 in the control group. The independent sample t-test yielded a significance value of 0.000 (<0.05), demonstrating a statistically significant effect of the treatment. The findings are consistent with Self-Determination Theory (SDT), which highlights the importance of relatedness, competence, and autonomy in promoting learning motivation and self-assurance. Short-form videos are recommended by the research as a new way to boost students' speaking confidence during English language training.